Implementasi Kurikulum Mardeka pada Masa Transisi dari K13 menuju Kurikulum Mardeka di Sekolah Dasar - Rusmita, Santi; Fitriyeni (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The purpose of this study is to describe the implementation of the independent learning curriculum during the transition period from the 2013 curriculum. This study uses a qualitative approach with a descriptive research type. This research was conducted by SDIT Nizhammuddin. The research subjects were 3 teachers who pursued the independent curriculum in selected classes. Data collection techniques were by using observation and interviews. Data were analyzed using several questions, research methods include types of research, research subjects and participants, research instruments, data collection and data analysis methods. The results of the study show that SDIT Nizhammuddin has implemented the Independent Learning curriculum. Through the transition period, there are many differences between the 2013 Curriculum and the Independent Curriculum. These differences follow the subject units, learning hours, learning implementation, learning strategies and the process of assessing graduation competency standards, etc. Curriculum 13 has a clear goal to shape the character of the nation while the objectives of the independent curriculum lessons are presented in learning outcomes (CP). The independent curriculum also has assessment assessments, namely non-cognitive and cognitive, where non-cognitive is indicated for assessment outside of learning while cognitive is an assessment in terms of knowledge.